ANALISIS Escherichia coli DAN HIGIENE SANITASI PADA MINUMAN ES TEH YANG DIJUAL DI PAJAK KARONA JAMIN GINTING KECAMATAN MEDAN BARU TAHUN 2013 - rima dani ritonga; irnawati marsaulina; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Iced tea is a traditional beverage which favored by many people. Iced tea could be contaminated by bacteria if not better way of processing. One of the bacteria that can contaminate is Escherichia coli which is an indicator of fecal coliforms and if drinking water contaminated by E. coli is the possibility that has been contaminated by human feces. This study aims to determine the content of Escherichia coli in iced tea and also hygiene and sanitation management iced tea in pajak karona jamin ginting kecamatan medan baru in 2013. The method used is a descriptive survey. The data obtained through observations and laboratory tests. Based on the survey results revealed that all examined iced tea have been contaminated by Escherichia coli is 7 samples 240 MPN, 2 samples 96 MPN and 1 sample 27 MPN. This is unqualified with Permenkes RI No.492/Menkes/Per/IV/2010 which states that the amount of content of E. coli in drinks is 0/100 ml sample. The presence of E. coli in iced tea may contaminated by human feces. Possible contamination of iced tea can be caused by lack of hygiene in the processing of iced tea, because based on observations obtained that all merchants have not applied the principles of hygiene and sanitation. To handle and restain the situation need to prevent the holding of inviligation and controlling by the relevant agencies (Departemen Kesehatan) about the importance of hygiene and sanitation iced tea. Keywords : Ice tea, Hygiene and Sanitation, Escherichia coli.